The Influence of Transformational Leadership, Organizational Climate, and Job Satisfaction on Improving Organizational Citizenship Behavior (OCB) - linawati, linawati; sumardi, Sumardi; E. Patras, Yuyun (Educational Researcher Journal, 2025)
This study aims to determine the influence of transformational leadership, organizational climate, and job satisfaction on improving teachers’ Organizational Citizenship Behavior (OCB) in private elementary schools in East Bogor District. OCB represents voluntary and extra-role behaviors that enhance organizational effectiveness and collaboration among teachers. The research employed a quantitative approach using a correlational survey design combined with the SITOREM (Scientific Identification Theory to Conduct Operation Research in Education Management) method to identify indicators that need improvement or maintenance. A total of 119 permanent teachers were selected through proportional random sampling. Data were collected through validated and reliable questionnaires (reliability coefficients: OCB = 0.89; transformational leadership = 0.87; organizational climate = 0.88; job satisfaction = 0.87). The results showed a strong positive and significant relationship between transformational leadership and OCB (r = 0.787, p < 0.01), a moderate but significant relationship between organizational climate and OCB (r = 0.475, p < 0.01), and a strong relationship between job satisfaction and OCB (r = 0.610, p < 0.01). Collectively, these three variables contributed 66.6% to the improvement of OCB. The SITOREM analysis highlighted priority indicators to be improved, including vision, job characteristics, collegial relations, communication, and work autonomy, while maintaining inspirational motivation, intellectual stimulation, charisma, and altruism. The study concludes that strengthening transformational leadership, fostering a positive organizational climate, and enhancing job satisfaction can significantly improve teachers’ OCB, leading to more effective and dynamic educational organizations.